The Influence Of Pedagogical Competency And Competency Professional Impact On Teacher Performance - Anggraini, Yola Putri; Norawati, Suarni; Syahsudarmi, Siti (International Journal of Law Policy and Governance, 2025)
This study aims to analyze the influence of pedagogical competence and professional competence on teacher performance at SDN 001 Panipahan, Pasir Limau Kapas District, Rokan Hilir Regency. The study used a quantitative approach with a survey method; the population and sample were all school teachers (n = 32) who were used as census samples. Data were collected through a Likert-based questionnaire, interviews, observations, and document reviews. The analysis included instrument validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS. The results show that pedagogical competence has a positive and significant effect on teacher performance, as does professional competence. Simultaneously, both variables significantly influence teacher performance. Furthermore, both variables are able to explain 74.9% of the variation in teacher performance. The findings indicate that improving both competencies is important for optimizing teaching performance. It is recommended that schools improve professional development programs (workshops, academic supervision, and the use of ICT) and encourage pedagogical training that emphasizes learning theory, learning strategies, and authentic assessment.